Effects of Climate Change on Local Economic Development in Ghana, and Resilience Measures to Promote Sustainable Rural Development - Essuman, Bismark (My University, 2022)
According to the Ghana Meteorological Agency, historical climatic data from 1960 to 2000 show a consistent and obvious rise in temperature and a corresponding decline in rainfall across all biological zones. Rainfall in the Semi-Deciduous Forest zone is anticipated to increase by 2.8%, 10.9%, and 18.6%, respectively, in 2020, 2050, and 2080. These figures and estimates are concerning given Ghana's population of 31.07 million, with agriculture employing around 52% of the labor force, services employing 29%, and industry employing 19%. Women account for around 39% of the agricultural labor force. Agriculture accounts for 54% of Ghana's GDP, more than 40% of export revenues, and more than 90% of the country's food needs. These initiatives highlight agriculture's significant contribution to national and local economic development. Agriculture is the backbone of most rural economies in Ghana; thus, these data and projections are concerning, given the rise in temperature and decrease in rainfall, which would impede most agricultural activity in rural areas. Climate change poses a threat to national development, necessitating the development of a resilience strategy to mitigate its effects. Because local economic development is a crucial part of forward-thinking local growth, climate change has an impact on it. In order for local and regional governments to effectively respond to the most urgent demands of the local community, local economic development is a crucial duty of local government. More than merely economic growth, local economic development also requires fostering participation and community dialogue and connecting people with resources. It is important to examine climate change and create resilience strategies to lessen the problems it provides in rural communities in order to increase employment and quality of life for both men and women in rural Ghana.
Keywords: Local Economic Development; Climate Resilience; Rural Welfare